2018
DOI: 10.1016/j.healthplace.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of travel distance and price promotions in tobacco product purchase quantity

Abstract: Regulatory action that imposes restrictions on the availability or use of price promotions could alter the purchasing behavior of rural Americans in such a way that makes it easier to reduce tobacco use or quit. Such action would also restrict flexibility in the price of tobacco products, which is known as a powerful tobacco control lever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…Unfortunately, we were unable to find any existing research that examined the relationship between exposure to price promotions and tobacco purchases. The only related study examined the relationship between the use of price promotions when making a tobacco purchase and the size of the purchase [14]. Despite the lack of research on the impact of price promotions on purchases in the United States, bans on price promotions have been cited as one of the most effective tobacco control efforts in Europe [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, we were unable to find any existing research that examined the relationship between exposure to price promotions and tobacco purchases. The only related study examined the relationship between the use of price promotions when making a tobacco purchase and the size of the purchase [14]. Despite the lack of research on the impact of price promotions on purchases in the United States, bans on price promotions have been cited as one of the most effective tobacco control efforts in Europe [19].…”
Section: Discussionmentioning
confidence: 99%
“…Promotions are used by tobacco companies to offset price increases caused by tobacco control policies, such as taxes [13]. Promotions have been associated with current smoking among youth [4] and purchasing larger quantities of cigarettes per store visit among adult smokers [14]. Researchers found that New York State counties with a greater number of retail cigarette promotions between 2004 and 2008 also had a higher youth smoking prevalence [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A uniform grid unit method for geospatial distribution of tobacco retailers, with larger grid units in rural versus urban areas, is recommended. 71 Tobacco retail accessibility may play an important role in individual smoking behaviour, particularly in rural areas, 72 but remains largely unexplored. Specific measures of retail accessibility, such as travel time by car, should be considered in the PhenX Toolkit of recommended measures for tobacco regulatory research.…”
Section: Reviewmentioning
confidence: 99%
“…Another study published in Health & Place (Doogan et al, 2018) used EMA to investigate whether in rural settings distance from home to the nearest tobacco outlet and the presence of price promotions interactively influenced quantities of tobacco purchased. Over 7-10 days (once per year over 2 years), 54 combustible and 27 smokeless tobacco users reported information on smartphones after every tobacco purchase (products, quantity, use of price promotions) as soon as possible after the purchase.…”
Section: A Review Of Selected Ema Studiesmentioning
confidence: 99%